A Research Agenda for Graduate Education - Mitchell, Brian S., 1962- (Book collections on Project MUSE., 2021)
"Post-baccalaureate education continues to expand at an accelerated rate as new degree programs are developed, enrollments rise, online instruction matures, and the number of institutions offering advanced degrees increases. Our level of understanding of graduate and professional education has not kept pace, especially in comparison to the depth of scholarship available on primary, secondary, and baccalaureate education. A Research Agenda for Graduate Education is a call to action for the graduate education community to commit to the same level of research and scholarship on itself that it expects from its students in their own disciplinary training. In this book, Brian S. Mitchell explores the current literature on graduate education for theoretical models that need testing, previous research that needs updating, and future research that may be explored. The book is divided into research questions on the science of graduate learning, graduate student career preparation, and graduate program improvement with special attention placed on current research topics. Targeted to higher education researchers, including educational psychologists and disciplinary-based researchers specializing in graduate education, this volume will also be of interest to funding agencies, university administrators, and faculty mentors."--